2014
DOI: 10.1037/a0035989
|View full text |Cite
|
Sign up to set email alerts
|

Impaired trace fear conditioning and diminished ERK1/2 phosphorylation in the dorsal hippocampus of adult rats administered alcohol as neonates.

Abstract: Utilizing a rat model of fetal alcohol spectrum disorder (FASD), ethanol was administered over postnatal days (PD) 4 to 9. As adults, control and ethanol rats underwent trace fear conditioning (TFC), in which a tone conditioned stimulus (CS) and footshock unconditioned stimulus (US) were repeatedly paired, though the two stimuli never overlapped in time. Following training in Experiment 1, conditioned fear (freezing) to the tone CS was dose-dependently reduced in ethanol rats relative to controls. Experiment 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
15
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 78 publications
3
15
2
Order By: Relevance
“…Previous research from our laboratory demonstrated no differences in CS-evoked freezing behavior between control and 5E treatment groups during the TFC session (DuPont et al, 2014), indicating intact sensory/motor responding and associative learning for both groups. The current study expands on our previous results by comparing SI and 5E freezing percentages during the 15-second tone CS and, following its offset, the 30-second TI.…”
Section: Trace Fear Conditioningmentioning
confidence: 92%
See 3 more Smart Citations
“…Previous research from our laboratory demonstrated no differences in CS-evoked freezing behavior between control and 5E treatment groups during the TFC session (DuPont et al, 2014), indicating intact sensory/motor responding and associative learning for both groups. The current study expands on our previous results by comparing SI and 5E freezing percentages during the 15-second tone CS and, following its offset, the 30-second TI.…”
Section: Trace Fear Conditioningmentioning
confidence: 92%
“…Rats were weaned on PD 21, same-sex group housed until PD 60 and, consistent with our previous studies, individually housed until sacrificed (DuPont et al, 2014;Goodfellow and Lindquist, 2014). Testing occurred between PD 65 to 75 around midday (~1100 to 1500) during the light phase (12-hour light/dark cyclelights on at 0600).…”
Section: Subjects and Neonatal Treatmentmentioning
confidence: 93%
See 2 more Smart Citations
“…Detailed reviews of these upstream YAP regulators can be found elsewhere [80,81]. Serum-derived small molecules sphingosine-1-phosphate (S1P) and lysophosphatidic acid (LPA) are particularly interesting because they are the first extracellular diffusible factors regulating YAP activity [82,83].…”
Section: Yap Mrna Transcriptionmentioning
confidence: 99%